Genomic mechanisms of plant growth-promoting bacteria in the production of leguminous crops - Adedayo, Afeez Adesina; Babalola, Olubukola Oluranti (Frontiers in Genetics, 2023)
Legumes are highly nutritious in proteins and are good food for humans and animals because of their nutritional values. Plant growth-promoting bacteria (PGPR) are microbes dwelling in the rhizosphere soil of a plant contributing to the healthy status, growth promotion of crops, and preventing the invasion of diseases. Root exudates produced from the leguminous plants' roots can lure microbes to migrate to the rhizosphere region in other to carry out their potential activities which reveals the symbiotic association of the leguminous plant and the PGPR (rhizobia). To have a better cognition of the PGPR in the rhizosphere of leguminous plants, genomic analyses would be conducted employing various genomic sequences to observe the microbial community and their functions in the soil. Comparative genomic mechanism of plant growth-promoting rhizobacteria (PGPR) was discussed in this review which reveals the activities including plant growth promotion, phosphate solubilization, production of hormones, and plant growth-promoting genes required for plant development. Progress in genomics to improve the collection of genotyping data was revealed in this review. Furthermore, the review also revealed the significance of plant breeding and other analyses involving transcriptomics in bioeconomy promotion. This technological innovation improves abundant yield and nutritional requirements of the crops in unfavorable environmental conditions.